Olivia Arévalo Lomas: a window from infinity Murder of the sacred song Shipibo-konibo-xeteba (2019)
This article presents a reflection on the ancestral indigenous wisdom of a people from the Peruvian Amazonia based on the murder of a wise woman. The documentary theoretical analysis aims to understand the socio-cultural ethosof the Shipibo-konibo-xeteba indigenous people, and the milestone that evidences the attempt to take over ancestral wisdom in the most violent way in the contemporary world: the murder of the spiritual master Olivia Arévalo, a real human treasure. The method consisted of a systematic and synthetic review of the Shipibo-Konibo people. The results presented here may contribute to promoting interest in studying the female leadership of the indigenous peoples and, at the same time, it challenges the academic and political community regarding the assassinations of indigenous leaders in different territories of Latin America. This is also a contribution to the visibility, recognition and dissemination of the intangible cultural heritage of the current diversity in the continent.